Clinical and Biochemical Profile of Libyan Patients with Serology and Biopsy Proven Celiac Disease - Samira Alkuni; Fatima Elhawil; Salma Sanok; Rabea Markus; Mohamed Frandah (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Celiac disease is a long-term immune disorder that primarily affects the small intestine. Iron deficiency anemia is the most widely experienced anemia in humans, which is a common extra intestinal manifestation of celiac disease. The aim of the current study is to describe the clinical and biochemical profile of adult Libyan celiac disease patients. Method. This was a case series study conducted by reviewing the medical records of the 100 patients diagnosed as celiac disease and followed in gastro-enterology clinic in Tripoli university hospital during the study period. A relevant data obtained from the records in a preformed case sheet. Result. The total number of celiac disease patients was 100 patients. Of them, 88 patients were females (88%) and 12 patients were males (12%). Patient age during the study were from 15 years to 45 years. Total villous atrophy (type3 lesion) was the commonest histopathological finding (62%) and subtotal villous atrophy in (38%) and none had T-Cell Lymphoma. About 9% of patients were asymptomatic and 91% symptomatic. Gastrointestinal symptoms (diarrhea in 60%, weight loss in 24%, and 17% of patients with abdominal distension), non- gastrointestinal symptoms like skin disorders (dermatitis herpetiformis) were diagnosed in 4 patients 4%. While, neuropsychiatric disorder (depression) was seen in 1 patient 1%, osteopenia in 2 patients 2% (low vitamin D and low serum Ca+2 and Mg+2), 5% of patients had raised AST and ALT, and prolonged PT in 3%. Conclusion. There was significant correlation between female patients having iron deficiency anemia and/or diarrhea to be celiac disease. Female patients present with iron deficiency anemia and / or diarrhea should be routinely screened for celiac disease by serological tests and then confirmed by endoscopic small bowel biopsies.